Power and responsibility: Advertising self‐regulation and consumer protection in a digital world. Issue 2 (29th January 2020) - Dickinson‐Delaporte, Sonia; Mortimer, Kathleen; Kerr, Gayle; Waller, David S; Kendrick, Alice
Abstract: While advertising self‐regulation is generally considered effective in a closed, largely country‐based system, the digital world in which we now live is an open and global system. This raises challenges for consumer protection from national regulators trying to enforce compliance from global media platforms, advertisers, and consumers. Applying the power‐responsibility equilibrium, this study explores who has the power and who has the responsibility for advertising self‐regulation in a digital world. In doing so, it takes an ethnographic approach, eliciting insights from 18 key stakeholders in the self‐regulatory process, across the three geographical areas of Europe, United States, and Asia‐Pacific. The findings highlight the need for more collaboration and alignment of self‐regulatory systems and build a framework for action through embedding responsibility, aligning standards, initiating processes, and improving outcomes. Six recommendations are offered to restore the balance of power and responsibility.